2017
DOI: 10.18632/oncotarget.15405
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine administered pregnant rats impair learning and memory in offspring via the CREB pathway

Abstract: Ketamine has been reported to impair the capacity for learning and memory. This study examined whether these capacities were also altered in the offspring and investigated the role of the CREB signaling pathway in pregnant rats, subjected to ketamine-induced anesthesia. On the 14th day of gestation (P14), female rats were anesthetized for 3 h via intravenous ketamine injection (200 mg/Kg). Morris water maze task, contextual and cued fear conditioning, and olfactory tasks were executed between the 25th to 30th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Previous studies have reported that ketamine damages nerve cells (Li X. et al, 2017 ). Using 1 mg/kg of ketamine in young male monkeys led to permanent and irreversible damage to brain function (Sun et al, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that ketamine damages nerve cells (Li X. et al, 2017 ). Using 1 mg/kg of ketamine in young male monkeys led to permanent and irreversible damage to brain function (Sun et al, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…There is considerable body of evidence to show that activation of ERK (p-ERK) in the hippocampus enhances memory via phosphorylation of the downstream transcription factor CREB on Ser residue 133 [ 32 ]. Low expression of CREB can lead to significant damage to the memory [ 33 , 34 ], while high expression of CREB can result in significant enhancement of memory and an improvement on social cognitive function [ 35 ]. Results from Figure 8 have shown that ketamine injection significantly reduced the level of the ERK, p-ERK, MSK, CREB, and p-CREB proteins in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies included a goat LOX-1 neutralizing antibody (R&D, Minneapolis, MN, USA) at a final concentration of 10 lg mL À1 , 38 a goat dectin-1 neutralizing antibody (R&D) at a final concentration of 30 lg mL À1 , a goat OPN neutralizing antibody (R&D) at a final concentration of 10 lg mL À1 39 and a control goat IgG (R&D). Inhibitors included the JNK inhibitor SP600125 (SelleckChem, Houston, TX, USA) (40 lmol L À1 ), 40 the Erk1/2 inhibitor SCH772984 (SelleckChem) (10 lmol L À1 ) 41 and the 4E-BP1/eIF4E interaction inhibitor 4E1RCat (SelleckChem) (50 lmol L À1 ). 42 HCECs were treated with human osteopontin recombinant protein (rhOPN; R&D Systems) at a final concentration of 180 ng mL À1 ) 43 or 4E1RC at 1 h after treatment with the OPN neutralizing antibody.…”
Section: In Vitro Experimentsmentioning
confidence: 99%